Impact of Social Economy on the Environmental Protection - SUTBAYEVA, Raikhan; BEISENGALIYEV, Berik; MADIYAROVA, Diana; TUREKULOVA, Assiya; KAPENOVA, Asemgul (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.v12.3(51).09, 2021)
Global challenges and threats, which inevitably affect the entire world community, naturally enhance the interdependence of states, require their joint actions aimed at solving social and economic problems of the world economy. As a result, the influence of social policy in the field of organizing and financing the social sphere, where environmental protection is an important factor, increases. Many processes occurring in the modern economy contribute to an increase in the importance of employers in solving modern problems of sustainable socio-economic development, both nationally and internationally. The level where rising unemployment rates have a significant negative impact on environmental priorities.